Meditation-based intervention for obsessive-compulsive disorder: A PRISMA-compliant systematic review and meta-analysis. Issue 30 (29th July 2022) - Lee, Si Myeong; Suh, Hyo-Weon; Kwak, Hui-Yong; Kim, Jong Woo; Chung, Sun-Yong
Abstract : Background: The purpose of this study was to investigate the effects of the meditation-based intervention on obsessive-compulsive disorder (OCD). Methods: The following databases were searched up to April 2021: the Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, Medline (via PubMed), PsycARTICLES, 4 Korean databases (Korean Medical Database [KMbase], Koreanstudies Information Service System [KISS], National Digital Science Library [NDSL], and Oriental Medicine Advanced Searching Integrated System [OASIS]), and China National Knowledge Infrastructure (CNKI). The search terms related to meditation-based intervention and OCD were used. This systematic review was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The selected articles were evaluated using the Cochrane risk of bias tool. The Review Manager (RevMan) 5.4 was used to perform the meta-analysis. Results: In all, 16 randomized controlled trials were selected. The meta-analysis showed that the group receiving the treatment combining medication and meditation-based intervention for OCD showed a more significant post-treatment improvement in Yale-Brown obsessive compulsive scale than the group receiving medication only. Compared with other non-medication interventions that are known to be effective in treating OCD, the Yale-Brown obsessive compulsive scale showed a significant improvement immediately after the meditation-based intervention. However, no significant difference was found in the follow-up monitoring data across all examined cases. Conclusion: This study was conducted to verify the effects of meditation-based intervention on OCD. The results suggested that combined treatment with medication and meditation-based intervention was more effective in treating OCD than medication alone; the positive effects of meditation-based intervention may be greater than the effects of other non-medication interventions. However, the lack of significant difference in the follow-up indicates that long-term effect of meditation-based interventions is unclear. Trial registration number: PROSPERO CRD42021244408